2020
DOI: 10.1186/s12872-020-01553-7
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive marker for evaluation of hypertensive heart disease: extracellular volume and myocardial strain

Abstract: Background: Evaluation of tissue fibrosis and myocardial hypertrophy in left ventricular (LV) remodeling is the basis of post-treatment evaluation of hypertensive heart disease (HHD). Extracellular volume (ECV) and myocardial strain parameters can indirectly reflect the changes of both. Our objective was to analyze the characteristics of ECV and strain parameters in LV myocardium of HHD with varying degrees of systolic dysfunction, and to explore the changes of both after treatment for hypertension. Methods: A… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 21 publications
2
16
0
Order By: Relevance
“…Similarly to speckle tracking echo, feature-tracking derived strains were all demonstrated to be altered in patients affected by AH, strains being more impaired in patients with LVH [84]. In patients with hypertensive heart disease MRI-derived strains were related to both left ventricular mass and ECV [85]. The negative association between GLS by feature tracking and concentric geometry evaluated by LVM/EDV ratio was also confirmed by MRI, similarly to 3Dechocardiography [86].…”
Section: Mrimentioning
confidence: 66%
“…Similarly to speckle tracking echo, feature-tracking derived strains were all demonstrated to be altered in patients affected by AH, strains being more impaired in patients with LVH [84]. In patients with hypertensive heart disease MRI-derived strains were related to both left ventricular mass and ECV [85]. The negative association between GLS by feature tracking and concentric geometry evaluated by LVM/EDV ratio was also confirmed by MRI, similarly to 3Dechocardiography [86].…”
Section: Mrimentioning
confidence: 66%
“…Several studies have shown impaired GLS in HTN LVH patients without LGE enhancement despite preserved LVEF [ 30 32 ]. GLS tracks myocardium deformation in long axis and disproportional LV thickening, while LVEF is a clinical measure of LV function.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that there is a major difference between simulations (~600 ms) and measurements in vivo (~80 ms). The primary cause of [30][31][32]. GLS tracks myocardium deformation in long axis and disproportional LV thickening, while LVEF is a clinical measure of LV function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, GRS was further validated to show significant discriminatory power for identifying LV outflow tract obstruction in patients with HCM ( 19 ). Based on the study from Niu et al, GRS improved obviously after treatment, which suggested that GRS might be an index for evaluating treatment ( 20 ). We also provided evidence that the variation and distribution of circumferential strain were similar to those of the radial orientation.…”
Section: Discussionmentioning
confidence: 99%